2018
DOI: 10.1097/mpg.0000000000002007
|View full text |Cite
|
Sign up to set email alerts
|

Value of Serum Zinc in Diagnosing and Assessing Severity of Liver Disease in Children With Wilson Disease

Abstract: Serum Zn is a novel parameter for diagnosis and correlates with severity of WD. The Proposed WD diagnostic score is useful while awaiting ATP7B mutation analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…A broadly modified version of the Leipzig score has recently been developed as a diagnostic scoring system specifically for children. [246] Its rationale is the need to avoid delayed diagnosis when there are difficulties getting ATP7B genotyping and/or liver parenchymal copper measurement. Histochemical assessment for hepatic parenchymal and a "triad" of biochemical parameters are substituted.…”
Section: Problemaɵcsee Tablementioning
confidence: 99%
“…A broadly modified version of the Leipzig score has recently been developed as a diagnostic scoring system specifically for children. [246] Its rationale is the need to avoid delayed diagnosis when there are difficulties getting ATP7B genotyping and/or liver parenchymal copper measurement. Histochemical assessment for hepatic parenchymal and a "triad" of biochemical parameters are substituted.…”
Section: Problemaɵcsee Tablementioning
confidence: 99%
“…Moreover, serum zinc is low in WD-induced ALF, thereby it appearing to be a novel parameter for diagnosis correlated with WD severity. 64 Likewise, a ratio of alkaline phosphatase to total bilirubin <4 and an AST to ALT ratio > 2.2 are regarded as highly sensitive and specific predictors of fulminant WD. 65 WD along with hepatitis B and AIH consist of the 3 exclusions, wherein an underlying preexisting hepatic condition should be ruled out before ALF is diagnosed.…”
Section: Clinical Presentation At Emergency Roommentioning
confidence: 99%
“…Most of the study showed low serum Zinc level in Wilson disease children. A study conducted by Palittiya Sintusek et al found serum Zn level was significantly lower in WD with acute liver failure patients compared to those with WD-non-ALF and ALF from indeterminate causes even when corrected serum Zn for low albumin & regardless of presentation, Zn levels showed a negative correlation with the disease severity [7].…”
Section: Introductionmentioning
confidence: 97%